Study on the velocity of droplet at steady state in contraction microchannels by numerical simulation - Nguyen, Thanh Tung; Hoang, Van Thanh; Luu, Duc Binh; Tran, Ngoc Hai; Tran, Minh Sang; Do, Le Hung Toan (Vietnam Journal of Mechanics, 2023)
The droplet-based microfluidic system is increasingly advancing and widely applied in various fields of analytical techniques and experiments. To optimize and advance this system, droplet dynamics is of utmost concern. The velocity of droplets is highly significant as it aids in precise droplet control and manipulation, ultimately leading to the optimization of device design and performance. This paper utilizes numerical simulations to explore the influence of flow characteristics, fluid properties, and geometric parameters of the contraction microchannel on the velocity of droplets while they are in a stable state. The findings indicate that the droplet velocity is influenced by factors such as viscosity ratio (λ), capillary number (Ca), and contraction ratio (C).